2020
DOI: 10.3389/fonc.2020.00943
|View full text |Cite
|
Sign up to set email alerts
|

Automated Radiotherapy Planning for Patient-Specific Exploration of the Trade-Off Between Tumor Dose Coverage and Predicted Radiation-Induced Toxicity—A Proof of Principle Study for Prostate Cancer

Abstract: Background: Currently, radiation-oncologists generally evaluate a single treatment plan for each patient that is possibly adapted by the planner prior to final approval. There is no systematic exploration of patient-specific trade-offs between planning aims, using a set of treatment plans with a-priori defined (slightly) different balances. To this purpose, we developed an automated workflow and explored its use for prostate cancer. Materials and Methods: For each of the 50 study patients, seven plans were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…On the contrary, in their multi-center study ( 37 ), the Erasmus-ICycle engine was used for MCO-based automation of prostate cancer planning in four Centers, reporting an overall dosimetric superiority of automated plans in terms of rectal dose reduction. The same research group used the ICycle engine to explore the patient-specific trade-offs between planning aims in prostate cancer ( 38 ). The authors reported significant NTCP reductions for rectal toxicity and underlined the role of automated approach for personalization of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in their multi-center study ( 37 ), the Erasmus-ICycle engine was used for MCO-based automation of prostate cancer planning in four Centers, reporting an overall dosimetric superiority of automated plans in terms of rectal dose reduction. The same research group used the ICycle engine to explore the patient-specific trade-offs between planning aims in prostate cancer ( 38 ). The authors reported significant NTCP reductions for rectal toxicity and underlined the role of automated approach for personalization of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the use of automated planning for development and evaluation of VMAT CSs has never been investigated for NPC. Many studies have demonstrated superior plan quality for automated planning compared to manual planning, for many tumor sites [14,[16][17][18][19][20][21][22][23][24][25][26][27]. Especially for development of CSs, high plan quality is required, as the aim is to in principle treat all future patients with the developed CS.…”
Section: Discussionmentioning
confidence: 99%
“…All plans used for this study were automatically generated with Erasmus-iCycle [14,15]. For many tumor sites, this system has demonstrated superiority of automatically generated plans, over manually generated plans [14,[16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: System For Automated Plan Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy planning aims to create a treatment that ensures adequate tumour volume irradiation to deliver the highest expected therapeutic ratio while limiting the dose to organs at risk (OARs) to maintain an acceptable toxicity profile. 4 There are secondary aims of ensuring a highly conformal prescription dose to the PTV and limiting the amount of radiation fall off away from the PTV.…”
Section: Introductionmentioning
confidence: 99%